EXPLORING E-PARTICIPATION POLICY AND INITIATIVES IN MALAYSIA - Nur Rusydina Khadzali; Zainal Md Zan2 (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The evolution of Information and Communication Technology (ICT) and the internet have affected the cultural, social, economic and political aspect throughout the world. It also greatly reshaped public administration in the last decade. The availability of internet and electronic medium also open the huge opportunity for public to participate and became closer to the government. New form of two-way communication for public and government officials have been developed and changed the landscape of local democracy. Consequently, in current digital era, the electronic participation or as known as e-participation as tools that encourage public participation has gained increasingly important. With the complexity of modern society today, e-participation helps to enhance the quality of participation. E-participation also could be the great complement to the traditional approach of public participation that may have some significance limitation in empowering the public participation. However, the discussion on the e-participation policy and initiatives in Malaysia still lacking and remains unclear. Therefore, this paper aims to comprehensively deliberate on the efforts that have been taken by the government towards the e-participation implementation. This paper also will provide an example of the experiences on the world’s best leaders in e-participation.